INTERACTIONS AS SOURCE OF THE CHANGE OF BEHAVIOR IN ADDICTION AND RECOVERY FROM ADDICTION. AN EXPLORATORY STUDY - VARGA, Claudia; COPOERU, Ion (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Based on the findings about the importance of social support network in the success of treatment and long term recovery, this article will provide an insight of the successful elements in addiction individual and group counseling interaction through which addicts manage to overcome the denial of addiction, to accept the recovery program, to go through the stages of recovery, and to identify appropriate research methods for understanding the phenomenon of interaction in recovery from addictions. This exploratory study will attempt to identify an innovative perspective of the aspects pertaining to the recovery from addiction which are susceptible to be disclosed primarily by using methods inspired by the analysis of interactions. The method used in research is qualitative focus group with addictions counsellors and people in recovery, working in a counseling center. Using the application of ELAN software to annotate and transcribe interactions from the video and audio recordings, it will situate the research on addiction and recovery from addiction in the larger field of investigations on communication processes in human interactions in various cultural, social and professional contexts.